Facies Characteristics, Depositional Environments and Sequences Stratigraphy of the Euphrates Formation in Hadetha Area, Western Iraq - Al-Ghreri, Mohamed Fahad; Al-Hetty, Salam Obied; Al-gibouri, Amer Sadie (Al-Nahrain Journal of Science, 2018)
The Euphrates Formation (Lower-early middle Miocene) shallow water carbonates, western Iraq was studied in order to determine its microfacies and depositional environment. According to the benthic foraminiferal assemblage along with other skeletal and non-skeletal components, Fourteen microfacies associations types (F1-F14) are recorded and distributed as: Lime mudstone, miliolids wackestone, alveolinids wackestone, echinoids wackestone, bioclastic packstone, peliods packstone, miliolids packstone, peneroplids packstone, rotaliids packstone, miliolids grainstone, peliods grainstone, ooids grainstone, miliolids-peneroplids grainstone, and peneroplids grainstone that were deposited in three facies belts, restricted marine, shoal, and open marine environments. Based on field observations, microfacies analysis and sequence stratigraphic concepts, the Lower Miocene successions is represented by four order cycles (A, B, C and D) they are mostly asymmetrical showing slightly lateral variation in thickness and symmetry. These cycles represent a succession episode of sea level rises and stillstands. The nature of these cycles reflects variation in the relative sea level resulted from eustatic and tectonic subsidence. Cycle A is underlain by Anah Formation, while cycle C is overlain by SB1 Fatha Formation. According to sequence development, the study area shows low rate of subsidence and the major controlling factor that effect is eustatic sea level fluctuation.